Molecular epidemiology of hepatitis A virus infection in Northeast India. Issue 7 (16th April 2015) - Bose, Moumita; Bose, Sujoy; Saikia, Anjan; Medhi, Subhash; Deka, Manab
Abstract The present study was undertaken to screen the molecular epidemiology of Hepatitis A virus (HAV) in Northeast India (NEI) who are ethnically distinct, tribal dominated and of lower socio‐economic status with almost no information available from NEI on these aspects. Briefly, 3 ml blood was collected from 324 random liver disease cases with jaundice, receiving care at Central Hospital, N.F. Railway, Guwahati, Assam with informed consent. The patients detected with HAV‐IgM positive status were included and were stratified as acute viral hepatitis (AVH) and fulminant hepatitis (FHF) based on clinical profile. Viral RNA was isolated and HAV‐RNA was detected by Real‐time PCR using primers for the VP3–VP1 region. HAV genotyping was studied by PCR‐direct sequencing‐phylogenetic analysis approach using the VP1/2A region of HAV isolates. Statistical analysis was performed using SPSS13.0 software. A total of 69 cases were HAV infected with two HBV co‐infected cases (n = 69 + 2 = 71), 62 cases and two co‐infected cases were AVH and others were FHF cases. HAV infection was predominant in especially in the young and adult age group. HAV‐RNA was detected in 28 cases, out of which 19 cases could be genotyped (12 AVH, 7 FHF); which showed the prevalence of genotype IIIA or IA only. Although HAV genotype IIIA was the major genotype in both the AVH (10/12, 83.33%) and FHF (5/7, 71.43%) group, but the difference in distribution of genotypes in AVH and FHF cases was statistically non‐significant (P = 0.550). HAV genotype IIIA is associated with the majority of HAV infected cases and severity in NEI. J. Med. Virol. 87:1218–1224, 2015. © 2015 Wiley Periodicals, Inc.